2022
DOI: 10.1183/13993003.02636-2021
|View full text |Cite
|
Sign up to set email alerts
|

Addition of bacterial filter alters positive airway pressure and non-invasive ventilation performances

Abstract: Recently, one manufacturer of home ventilators issued an alert regarding the potential risk of serious injury related to the use of some of their positive airway pressure (PAP) and non-invasive ventilation (NIV) devices [1]. The risk is caused by the polyurethane foam used in their ventilators. In some cases, the foam broke into the blower and could have been inhaled by patients. The manufacturer and some healthcare regulatory agencies advocated, as a temporary solution, to modify PAP and NIV circuits by addin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Three reports elaborated on the health risks of recalled PAP devices, such as cancer (Kendzerska et al, 2021;Palm et al, 2022;Wang and Xiao, 2022). One report examined whether recalled PAP devices could be modified to reduce risks (Rabec et al, 2022). In our domain of organizational case studies, we found two accounts, one from Mayo Clinic (Morgenthaler et al, 2022) and one from the Cleveland Clinic (Lance et al, 2022).…”
Section: Introduction Nature Of Problem Being Addressedmentioning
confidence: 95%
“…Three reports elaborated on the health risks of recalled PAP devices, such as cancer (Kendzerska et al, 2021;Palm et al, 2022;Wang and Xiao, 2022). One report examined whether recalled PAP devices could be modified to reduce risks (Rabec et al, 2022). In our domain of organizational case studies, we found two accounts, one from Mayo Clinic (Morgenthaler et al, 2022) and one from the Cleveland Clinic (Lance et al, 2022).…”
Section: Introduction Nature Of Problem Being Addressedmentioning
confidence: 95%
“…Therefore, the interposition of viral–bacterial filters in the inspiratory limb was recommended. However, a bench study showed that the addition of such filters had adverse effects on ventilator performance, with an increase in the product pressure time required to activate the trigger (PTPtrig), lower pressurisation and lower tidal volume [ 29 ]…”
Section: Filters and Other Itemsmentioning
confidence: 99%
“…
We read the innovative study by RABEC et al [1] with great interest, in which they evaluated the impact of use of different inline bacterial filters on the performance of non-invasive ventilator (NIV) using positive inspiratory pressure (PIP) ventilation. After analysing the study, we want to raise some points which are vital in interpreting the outcomes of this study.While inline placement of bacterial filter will obviously protect against inhalation of any broken parts of the NIV machine, they are known to affect the overall performance of the NIV.
…”
mentioning
confidence: 99%
“…We read the innovative study by RABEC et al [1] with great interest, in which they evaluated the impact of use of different inline bacterial filters on the performance of non-invasive ventilator (NIV) using positive inspiratory pressure (PIP) ventilation. After analysing the study, we want to raise some points which are vital in interpreting the outcomes of this study.…”
mentioning
confidence: 99%